2019
DOI: 10.1016/j.chb.2018.12.043
|View full text |Cite
|
Sign up to set email alerts
|

“I cannot live without my [tablet]”: Children's experiences of using tablet technology within the home

Abstract: Highlights:  Tensions exist between parents and children regarding domestic tablet device use.  Varied and covert techniques were reported to evade any parental tablet limitations.  Many children did not have clear boundaries for their home use of tablet technology.  For some children tablet use may be problematic as symptoms of addiction were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…We noted several cases where parental rules and boundaries around cyber-security in the home was associated with tensions between parents and children, around access to devices, allowable apps, websites and social media platforms, and privacy and security measures used by children. Our findings echo those around tensions in family technology use in other research, reporting that parents trying to restrict device use for their children causes arguments and tensions in the home (Hadlington et al, 2019). Interestingly, parents in our study were cognizant of the fact that these challenges and tensions between parents and children are the same as those of previous generations, but the context is different.…”
Section: Negotiation Of Cyber-security Boundariessupporting
confidence: 85%
See 1 more Smart Citation
“…We noted several cases where parental rules and boundaries around cyber-security in the home was associated with tensions between parents and children, around access to devices, allowable apps, websites and social media platforms, and privacy and security measures used by children. Our findings echo those around tensions in family technology use in other research, reporting that parents trying to restrict device use for their children causes arguments and tensions in the home (Hadlington et al, 2019). Interestingly, parents in our study were cognizant of the fact that these challenges and tensions between parents and children are the same as those of previous generations, but the context is different.…”
Section: Negotiation Of Cyber-security Boundariessupporting
confidence: 85%
“…Prior research has examined such processes of negotiation in the context of technology use in the family home. For instance, there is evidence for conflict in parent-child relationships when parents try to restrict children's use of technology like tablets (Blum-Ross and Livingstone, 2016;Hadlington et al, 2019). This conflict is even more evident when children take the lead in technology use in the home, as traditional power roles of parents versus their children are reversed (Holloway and Valentine, 2002;Nelisson and Van den Bulck, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the factors mentioned earlier, it was anticipated that an underage social media user could quickly fabricate his personal information to get access to social media gambling activities (Chou et al, 2019), thus concealing actual use of social media networks parents. This is also supported by Hadlington et al (2019), who found evidence that children have deceptive strategies to play games on their digital devices. In addition, most parents were found to lack an understanding of the rules and boundaries concerning social media use at home.…”
Section: Social Interaction and Diversion Motivesmentioning
confidence: 58%
“…We specifically noticed that smartphone use immediately prior to going to sleep and after waking up was talked about by our participants in the interviews, but they did not record these moments in the Subfilms, which is, although not surprising given the nature of the technique, problematic since smartphone use habits seem to be intimately interwoven with sleep (e.g. [9,34]). A detailed investigation of in situ smartphone use connected to sleep, although difficult, would provide a tremendous contribution to our understanding of smartphone use.…”
Section: Limitationsmentioning
confidence: 99%